Critical Thinking Skills Through Literacy and Numeration Oriented Mathematics Student Worksheet - Meggy Novitasari; Sabar Narimo; Denisa Nurul Fajri; Aliifah Raisia (Jurnal Basicedu, 2022)
The research objective in this article is to describe critical thinking skills through the Student Worksheet (LKPD) which is oriented towards numeracy literacy which has three aspects, namely 1) analyzing the problem, 2) completing the sheet, and 3) drawing conclusions. The type of research in this article is descriptive qualitative. Data collection techniques with participatory observation, deepening, and document analysis. Data validation performed by triangulation of sources and time. The data analysis technique was done inductively. The results of the study, the ability to think critically through the numeracy-oriented Student Worksheet (LKPD) of mathematics can be divided into three. 1) analytical skills related to aspects of Identifying problems (questions) from various points of view by understanding concepts and developing problem strategies that are carried out by getting used to analyzing problems in Mathematics Student Worksheets that are oriented towards numeracy literacy. 2) Aspects of problem solving abilities related to problem solving indicators, students are able to solve problems and think logically and concept development needs to be familiarized. 3) The ability to think critically on indicators related to the communication of new ideas still needs to be familiarized and communicated in everyday contexts.